Incentivos fiscais à pesquisa, desenvolvimento e inovação tecnológica no Brasil: uma análise da Lei do Bem - Faccini, Leandro Esperança (2015)
It appears that countries with developed or developing economies have some kind of public policy for granting some kind of incentive to research and development of technological innovation. Incentives for research, development and innovation are generally divided into allowances and tax benefits. This division is regardless of the country's development level, it is more associated with the culture and historical uniqueness and not necessarily to economic power. Developed countries such as the United States, Canada, France and United Kingdom use the tax incentives model, but Germany encourages innovation through benefits, and all this is done based in laws. Brazil published its first legal regulations to encourage innovation in the 60s, when the legislation covered only the S&T activities (Science and Technology). There was a time when incentives did not improve and lasted until the mid-90s, a time when the country went through 21 years of military dictatorship, high inflation and very few financial resources available for investment. However, this scenario began to change in 1993 when it was published what is considered the first legislation on innovation in the country, Law No. 8,661 of June 2, 1993, starting then a time of reflection by the Brazilian authorities about the importance of innovation for the country s development, culminating in Law No. 11,196 of July 29, 2005, known as the Good Law, the most important legislation in Brazil on Research, Development and Innovation - R&D. Whereas the incentive rules to R&D in Brazil are still incipient, this work was intended to answer the following research question: the tax benefits introduced by public policies conducive to technological innovation, particularly the Good Law, are they properly contributing to stimulate technological innovation in Brazilian companies? Therefore, the research involved a short approach to the incentive practices of countries considered relevant in the global innovation scenario and assessed the main similarities and differences between the Brazilian practices and the international ones. The conclusion is that there are limitations on the Brazilian regulations for incentives in R&D, especially concerning the scope, since it does not allow incentives to reach small and medium businesses, delaying the emergence of cutting-edge technology in the country therefore less competitiveness of Brazilian products and services in the international market